PENERAPAN GERAK DAN LAGU DALAM MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI SPS AZ-ZAHRA KELURAHAN SUKAMULIA KECAMATAN SAIL KOTA PEKANBARU - Yenny Zain; Zulkifli N Zulkifli N; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This study aims to determine how big the Implementation of Motion and songs in order to improve gross motor skills Childhood 4-5 years. This study consists of two variables: Motion and Song and gross motor. The hypothesis of this study is the adoption of Motion and Song Can Improve gross motor development Childhood 4-5 Years at SPS Az-Zahra, Village Sukamulia, District Sail, Pekanbaru ". Methods of data collection in this study using observation and documentation. Data collection techniques in this research using descriptive qualitative data. The results showed there was a significant positive relationship between the adoption of the Motion and the song of the gross motor skills of children aged 4-5 years in early childhood in gross motor ability of children aged 4-5 years in the Az-Zahra SPS sub Sukamulia District of Sail Pekanbaru increased in each cycle. This is evident from the average acquisition value amounted to 44.2% of pre cycle, the first cycle of 54.3%, and in the second cycle of 79.6%.Keywords: Motion and Song, Motor Rough